The ENCIC-CT Model for the Development of Critical Thinking - Franco-Mariscal, Antonio Joaquín; Cano-Iglesias, María José; España-Ramos, Enrique; Blanco-López, Ángel (Springer Cham, 2024)
The development of critical thinking among citizens is crucial for the advancement of humanity in a dynamic and ever-changing world. Therefore, it is essential to promote a critical understanding of the challenges we face as a society. Initially, this chapter addresses how various scholars have discussed and developed the construct of critical thinking from philosophical and cognitive psychology perspectives, with a particular emphasis on its integration into science education. Next, the ENCIC-CT model to critical thinking development is introduced. This framework was formulated during the research project that underpins this book, and guides its constituent chapters. This model proposes developing critical thinking in science education through daily life problems and includes three key domains of action: knowledge, skills, and dispositions. Each domain comprises different dimensions that can be addressed through scientific practices such as argumentation, inquiry, or modeling, using various teaching strategies including gamification/role-playing, micro-debates, augmented reality, controversy mapping, and multimedia resources such as digital storytelling, among others. This model can also be applied to the analysis and design of educational proposals in teacher training.
PID2019-105765GA-I00
Keywords: Ciencia - Estudio y enseñanza; Pensamiento crítico; Enseñanza de las ciencias; Modelo ENCIC-CT